Identification of the Physiologically Difficult Airway in the Pediatric Emergency Department. (3rd October 2020) - Dean, Preston N.; Hoehn, Erin F.; Geis, Gary L.; Frey, Mary E.; Cabrera‐Thurman, Mary K.; Kerrey, Benjamin T.; Zhang, Yin; Stalets, Erika L.; Zackoff, Matthew W.; Maxwell, Andrea R.; Pham, Tena M.; Lautz, Andrew J.
Abstract: Background: The risk factors for peri‐intubation cardiac arrest in critically ill children are incompletely understood. The study objective was to derive physiologic risk factors for deterioration during tracheal intubation in a pediatric emergency department (PED). Methods: This was a retrospective cohort study of patients undergoing emergency tracheal intubation in a PED. Using the published literature and expert opinion, a multidisciplinary team developed high‐risk criteria for peri‐intubation arrest: 1) hypotension, 2) concern for cardiac dysfunction, 3) persistent hypoxemia, 4) severe metabolic acidosis (pH < 7.1), 5) post–return of spontaneous circulation (ROSC), and 6) status asthmaticus. We completed a structured review of the electronic health record for a historical cohort of patients intubated in the PED. The primary outcome was peri‐intubation arrest. Secondary outcomes included tracheal intubation success rate, extracorporeal membrane oxygenation (ECMO) activation, and in‐hospital mortality. We compared outcomes between patients meeting one or more versus no high‐risk criteria. Results: Peri‐intubation cardiac arrest occurred in 5.6% of patients who met at least one high‐risk criterion compared to 0% in patients meeting none (5.6% difference, 95% confidence interval [CI] = 1.0 to 18.1, p = 0.028). Patients meeting at least one criterion had higher rates of any postintubation cardiac arrest in the PED (11.1% vs. 0%, 11.1% difference, 95% CI = 4.1 to 25.3, p = 0.0007), in‐hospital mortality (25% vs. 2.3%, 22.7% difference, 95% CI = 11.0 to 38.9, p < 0.0001), ECMO activation (8.3% vs. 0%, 8.3% difference, 95% CI = 2.5 to 21.8, p = 0.004), and lower likelihood of first‐pass intubation success (47.2% vs. 66.1%, −18.9% difference, 95% CI = −35.5 to −1.5, p = 0.038), respectively. Conclusions: We have developed criteria that successfully identify physiologically difficult airways in the PED. Children with hypotension, persistent hypoxemia, concern for cardiac dysfunction, severe metabolic acidosis, status asthmaticus or who are post‐ROSC are at higher risk for peri‐intubation cardiac arrest and in‐hospital mortality. Further multicenter investigation is needed to validate our findings.